Pengaruh Variasi Sudut Inlet Nozzle terhadap Performa Turbin Tesla pada Analisis Eksperimen, Teoritis, dan Simulasi CFD - Danur Riswanto (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
The bladeless Tesla turbine, which converts fluid momentum into rotary motion through viscous boundary-layer interaction with smooth parallel discs, has attracted renewed interest for micro-scale renewable energy applications. Despite this promise, optimizing the inlet nozzle geometry remains crucial to enhancing turbine performance under limited pressure and flow conditions. This study investigates the effect of varying nozzle inlet angles (10°, 20°, and 30°) on the performance of a Tesla turbine with a 19-disc rotor (95 mm diameter, 1.28 mm thickness, 0.6 mm spacing) operating with water at 5 PSI and a maximum flow rate of 4 LPM. A tri-method approach was adopted, combining physical experiments, analytical calculations based on rotational dynamics, and Computational Fluid Dynamics simulation using SolidWorks Flow Simulation. Results consistently demonstrate that the smallest nozzle angle (10°) delivers the highest performance: experimental efficiency of 0.147% and power of 0.140 Watt; theoretical efficiency of 0.23% and power of 0.34 Watt; and CFD-simulated efficiency of 0.340% and power of 0.748 Watt, with an average torque of 0.252 Nm. The findings confirm that a smaller nozzle angle extends the boundary-layer growth along the disc surface, thereby enhancing momentum transfer efficiency. This research provides a validated methodology for nozzle optimization applicable to pico-hydro renewable energy systems.